Sorafenib Attenuates Fibrotic Hepatic Injury Through Mediating Lysine Crotonylation - Chen XF; Ji S (Dove Medical Press, 2022)
Xiao-Feng Chen, Shaoxiu Ji School of Basic Medical Sciences, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of ChinaCorrespondence: Xiao-Feng Chen, School of Basic Medical Sciences, Chengdu University of Traditional Chinese Medicine, No. 1166, Liutai Avenue, Wenjiang District, Chengdu, People's Republic of China, Tel +86-28-61800219, Email xiaofengchen@cdutcm.edu.cnBackground: Liver fibrosis is an independent contributor of chronic liver diseases, and regressing liver fibrosis is considered a potential therapeutic target for chronic liver diseases. We aimed to explore the effects and mechanism of sorafenib in liver fibrosis.Methods: Male Sprague Dawley (SD) rats were subjected to subcutaneous injection of carbon tetrachloride (CCl4) for 8 weeks to induce liver fibrosis and then treated with sorafenib. The degree of liver fibrosis was analyzed by hematoxylin-eosin (H&E) staining, Masson staining, and Picrosirius red (PSR) staining. Serum biochemical indexes were detected by fully automatic biochemical analyzer or enzyme-linked immunosorbent assay (ELISA). Quantitative real-time polymerase chain reaction (qRT-PCR) was performed to detect the expression of pro-fibrotic genes. Immunohistochemical staining and Western blotting were carried out to evaluate the levels of lysine crotonylation.Results: Liver index was reduced with oral sorafenib in CCl4-induced rats. Serum liver function (alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBIL)) and fibrosis indicators (type III procollagen (PC-III), hyaluronic acid (HA), and laminin (LN)) were attenuated with sorafenib treatment. Sorafenib improved the hepatic structure and fibrotic progression. The expression of fibrosis-related genes was remarkely reduced with sorafenib treatment. Meanwhile, sorafenib inhibited α-SMA and collagen I cumulation induced by CCl4 injection. Besides, protein lysine crotonylation especially the crotonylated H2BK12 (H2BK12cr) and crotonylated H3K18 (H3K18cr) were reversed by sorafenib, which were decreased in response to CCl4 treatment. Spearman correlation analysis shown lysine crotonylation expression was negatively correlated with serum fibrotic indicators. Conversely, crotonylation-regulated enzymes, which negatively regulate protein crotonylation, were increased in response to CCl4 treatment, while sorafenib reduced their expression.Conclusion: Sorafenib exerts significant anti-fibrotic effects through mediating crotonylation-regulated enzymes and protein crotonylation in fibrotic rats.Keywords: liver fibrosis, sorafenib, crotonylation, epigenetic regulation